Membangun Rasa Kecintaan Generasi Milenial Kota Bandung kepada Makanan Minuman Tradisional Sunda - Dikdik Purwadisastra (Economics Professional in Action (E-Profit), 2020)
This study aims to determine the extent of Sundanese traditional food products to be the first choice for millennial generation, this research method is descriptive with a qualitative approach with 15 respondents with characteristics of respondents aged between 17-38 years, various professions. The results of the study obtained the majority of respondents around 66.7% know the traditional Sundanese products but it is unfortunate that the millennial generation Sundanese rarely consume traditional Sundanese food where there are about 40% rarely consume Sundanese traditional food even 26.7% of respondents answered never, the authors draw conclusions need the existence of product and service innovations to increase the sense of love of the Bandung City millennial community towards Sundanese traditional food / drinks.